Вплив дії розтягуючих напружень на структуру та властивості спеченого у вакуумі малокобальтового твердого сплаву ВК15 - Юрчук, М.О. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
The paper gives structural characteristics and values of the basic properties of WC–15Co lamented carbide in the form of rods sintered in vacuum under tensile stresses. The value of the ultimate load has been determined at which the cemented carbide fractures during sintering.